1996
DOI: 10.7556/jaoa.1996.96.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue complaints in primary care: Incidence and diagnostic patterns

Abstract: The complaint of chronic fatigue is ubiquitous in the primary care setting. Because of the nonspecific nature of chronic fatigue, practitioners do not focus on this complaint. Furthermore, most physicians use a problem-based approach. Such a prematurely narrowed focus could overlook the chronic fatigue complaint. Omissions in the data collection process would prove this oversight. Therefore, we postulated that a retrospective review of evaluations for chronic fatigue would demonstrate significant categorical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…14,17,19 Fatigue can be defined as an overwhelming sense of tiredness, lack of energy and a feeling of exhaustion, and im-paired physical and cognitive functioning, which needs to be distinguished from symptoms of depression, which include lack of self-esteem, sadness, and despair or hopelessness. [20][21][22][23] Occasional fatigue can be a part of the strain of everyday life; however, constant or frequent fatigue is suspected to be related to conditions of physical or psychological illness. 24 An epidemiological study measuring fatigue in a random sample of the general population reported no firm associations between fatigue and social variables, but fatigue seems to be highly prevalent in somatic and psychiatric disorders.…”
Section: Excessive Sleepiness and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…14,17,19 Fatigue can be defined as an overwhelming sense of tiredness, lack of energy and a feeling of exhaustion, and im-paired physical and cognitive functioning, which needs to be distinguished from symptoms of depression, which include lack of self-esteem, sadness, and despair or hopelessness. [20][21][22][23] Occasional fatigue can be a part of the strain of everyday life; however, constant or frequent fatigue is suspected to be related to conditions of physical or psychological illness. 24 An epidemiological study measuring fatigue in a random sample of the general population reported no firm associations between fatigue and social variables, but fatigue seems to be highly prevalent in somatic and psychiatric disorders.…”
Section: Excessive Sleepiness and Fatiguementioning
confidence: 99%
“…Either or both may be caused by various sleep-related disorders such as sleep apnea, periodic limb movement disorder (PLMD), narcolepsy, drug and alcohol abuse, psychiatric disorders, circadian rhythm disorders, medical disorders, and iatrogenic factors. [13][14][15]19,20 These common manifestations of sleep problems may have separate economic consequences because of different treatment requirements and distinct comorbidity profiles. Sleep restriction (the Toronto syndrome) is probably the most common cause of excessive sleepiness in North America and occurs as a result of inadequate sleep hygiene, in which individuals adapt their lifestyle to work and other commitments and compromise sleep time.…”
Section: Excessive Sleepiness and Fatiguementioning
confidence: 99%
“…Either or both may be caused by a broad range of sleep disorders, such as sleep apnea, periodic limb movement disorder, narcolepsy, psychophysiologic insomnia, circadian rhythm sleep disorders, chronic fatigue syndrome, fibromyalgia, alcohol and drug abuse, and psychiatric disorders (Abbey and Shapiro 1995; Hanly and Shapiro 1995; Lichstein et al. 1997; Ohayon and Shapiro 2000; Ward et al. 1996).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] It is not clear that any of these efforts have met with outstanding success. Such efforts have ranged from holding informal group meetings, to advocating sleep testing for sleep disordered breathing in the home, and even for nocturnal penile tumescence (NPT) measures in the home.…”
Section: Issue #1-can We Consider the Very High Prevalence Of Sleep Dmentioning
confidence: 99%